Banking on Governance? Conflicts of Interest Facing Bank Owners and Supervisors - Leechor, Chad (World Bank, Washington, DC, 2012)
Banks fail with alarming frequency, resulting in large losses of taxpayer money. A key factor in the high failure rate is the flawed governance mechanism, which exacerbates the risks inherent in banking. Bankers control a lot of other people's money and have much discretion over the information they disclose. The temptation to engage in excessive risk taking is strong. Tightening banking supervision is seldom the solution. For their part, banking supervisors often face incentives at odds with those of taxpayers. At times they may prefer not to act to minimize taxpayer losses. These twin governance problems are further compounded by the common practice of disclosing banking information only to supervisors, not to markets. This Note explains the conflicts and proposes some solutions.